Quercetin suppresses ROS production and migration by specifically targeting Rac1 activation in gliomas - Baba, Rafia A.; Mir, Hilal A.; Mokhdomi, Taseem A.; Bhat, Hina F.; Ahmad, Ajaz; Khanday, Firdous A. (Frontiers in Pharmacology, 2024)
P66Shc and Rac1 proteins are responsible for tumor-associated inflammation, particularly in brain tumors characterized by elevated oxidative stress and increased reactive oxygen species (ROS) production. Quercetin, a natural polyphenolic flavonoid, is a well-known redox modulator with anticancer properties. It has the capacity to cross the blood–brain barrier and, thus, could be a possible drug against brain tumors. In this study, we explored the effect of quercetin on Rac1/p66Shc-mediated tumor cell inflammation, which is the principal pathway for the generation of ROS in brain cells. Glioma cells transfected with Rac1, p66Shc, or both were treated with varying concentrations of quercetin for different time points. Quercetin significantly reduced the viability and migration of cells in an ROS-dependent manner with the concomitant inhibition of Rac1/p66Shc expression and ROS production in naïve and Rac1/p66Shc-transfected cell lines, suggestive of preventing Rac1 activation. Through molecular docking simulations, we observed that quercetin showed the best binding compared to other known Rac1 inhibitors and specifically blocked the GTP-binding site in the A-loop of Rac1 to prevent GTP binding and, thus, Rac1 activation. We conclude that quercetin exerts its anticancer effects via the modulation of Rac1-p66Shc signaling by specifically inhibiting Rac1 activation, thus restraining the production of ROS and tumor growth.